2019
DOI: 10.2136/sssaj2018.10.0376
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Requirements for Corn in North Dakota: Influence of Clay Mineralogy

Abstract: Use of dry soil K soil test was most predictive of corn response in North Dakota. Consideration of clay chemistry increased the prediction of yield response by the K soil test. A smectite/illite ratio of 3.5 separated the sites into one requiring a higher critical K soil test value and one with a lower critical K value. Due to initially high soil test K values, K soil test correlation and calibration for corn in North Dakota has previously not been intensely investigated. Potassium fertilizer rate experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…These are aligned in layers with spaces between them where water and nutrients can reside and specifically where K is attracted to negative charges produced within the structure of the minerals. In North Dakota, Breker et al (2019) identified the ratio of an expansible mineral, smectite, to another 2:1 phyllosilicate, illite, as an additional factor to soil‐test K for identifying different critical levels in soil. They reported a critical level of 200 ppm K when smectite/illite ratios were above 3.5, whereas below that ratio, the critical level was 130 ppm K. Greater amounts of smectite, the mineral that retains K in the interlayer spaces when dehydrated, resulted in a need for higher soil‐test K for optimum crop yield.…”
Section: Making Potassium Recommendationsmentioning
confidence: 99%
“…These are aligned in layers with spaces between them where water and nutrients can reside and specifically where K is attracted to negative charges produced within the structure of the minerals. In North Dakota, Breker et al (2019) identified the ratio of an expansible mineral, smectite, to another 2:1 phyllosilicate, illite, as an additional factor to soil‐test K for identifying different critical levels in soil. They reported a critical level of 200 ppm K when smectite/illite ratios were above 3.5, whereas below that ratio, the critical level was 130 ppm K. Greater amounts of smectite, the mineral that retains K in the interlayer spaces when dehydrated, resulted in a need for higher soil‐test K for optimum crop yield.…”
Section: Making Potassium Recommendationsmentioning
confidence: 99%
“…Crop nutrient management practices are usually based on soil‐test results that predict whether the soil contains sufficient plant‐available nutrients to produce maximal crop yield and recommend fertilizer when nutrient availability is below optimum. The accuracy of soil tests for identifying K‐deficient soils varies among soils and geographic areas but, as a general rule, soil tests for K availability are reasonably accurate (Barbagelata & Mallarino, 2013; Breker et al., 2019; Slaton, Golden, DeLong, & Mozaffari, 2010; Williams, Parvej, Holshouser, Frame, & Reiter, 2018). The weakest link of soil‐test‐based fertilizer recommendations involves the calibration of the fertilizer‐K rate required to maximize yield for a given soil‐test value.…”
Section: Introductionmentioning
confidence: 99%
“…The K budget at field scale (Benbi & Biswas, 1999;Yadvinder-Singh et al, 2004;Yang, Sun, & Zhang, 2014) and soil K test (Mallarino, Barbagelata, & Wittry, 2004;Yang et al, 2014) or estimated exchangeable K are often used to manage K over large agricultural areas (Bailey, 1983;Tan, Jin, Jiang, Huang, & Liu, 2012). While soil test critical K levels depend on clay mineralogy (Breker et al, 2019), the contribution of non-exchangeable K…”
Section: Introductionmentioning
confidence: 99%
“…The K budget at field scale (Benbi & Biswas, 1999; Yadvinder‐Singh et al., 2004; Yang, Sun, & Zhang, 2014) and soil K test (Mallarino, Barbagelata, & Wittry, 2004; Yang et al., 2014) or estimated exchangeable K are often used to manage K over large agricultural areas (Bailey, 1983; Tan, Jin, Jiang, Huang, & Liu, 2012). While soil test critical K levels depend on clay mineralogy (Breker et al., 2019), the contribution of non‐exchangeable K (Hinsinger, 2002; Lal, Swarup, & Singh, 2007; Rupa, Srivastava, Swarup, & Singh, 2001) or interlayer K (Hinsinger & Jaillard, 1993; Øgaard & Krogstad, 2005) to plant K uptake may be substantial. Hence, soil test K quantified only as exchangeable K appears to be insufficiently informative to determine soil K supply capacity (Cox, Joern, Brouder, & Gao, 1999; Habib et al., 2014).…”
Section: Introductionmentioning
confidence: 99%